Dark matter gravitational effects in the milky way (2020)
In this manuscript we proposed two methods to find possible measurable effects of Dark Matter in the galactic center of the Milky Way using the Navarro-Frenk-White density profile and the Burkert profile as basis for our review. The first method, an analysis on rotational curves to about 0-100pc from the central black hole, finds that if the galaxy is considered to be a NFW-type galaxy the Dark Matter effect is relevant and noticeable at close distances causing the rotational velocities to double at [at approximately] 90pc in comparison to a galaxy lacking of Dark Matter. The Dark Matter equals the blackhole?s influence at just [at approximately] 55pc. On the contrary, if the galaxy is better modeled by the Burkert profile, the Dark Matter relevance is negligible at close distances from the center. The second method relies on the potential derived from the profiles to find an effect on the gravitational redshift of stars positioned near the Milky Way's center. It is found that both profiles have similar effects on the redshift behavior, nonetheless, the results for z of NFW are up to 1.4 times of Burkert's. For the two profiles is shown that Dark Matter is the main source of redshift, since zDM /zBH increases with distance and is already [at approximately] 10 at just 10 pc from the black hole. At 15 pc the redshift is caused almost entirely due to the presence of Dark Matter. The consequences of this work are intriguing owing to the fact that usually Dark Matter effects are studied far away from the galaxy's center, whereas we found considerable effects at very close distances. The results are expected to be measurable or used to find the better profile parametrization for our galaxy